Binary neutron star merger simulations with neutrino transport and turbulent viscosity: impact of different schemes and grid resolution. Issue 1 (11th January 2023) - Zappa, Francesco; Bernuzzi, Sebastiano; Radice, David; Perego, Albino
ABSTRACT: We present a systematic numerical relativity study of the impact of different physics input and grid resolution in binary neutron star mergers. We compare simulations employing a neutrino leakage scheme, leakage plus M0 scheme, the M1 transport scheme, and pure hydrodynamics. Additionally, we examine the effect of a sub-grid scheme for turbulent viscosity. We find that the overall dynamics and thermodynamics of the remnant core are robust, implying that the maximum remnant density could be inferred from gravitational wave observations. Black hole collapse instead depends significantly on viscosity and grid resolution. Differently from recent work, we identify possible signatures of neutrino effects in the gravitational waves only at the highest resolutions considered; new high-resolution simulations will be thus required to build accurate gravitational wave templates to observe these effects. Different neutrino transport schemes impact significantly mass, geometry, and composition of the remnant's disc and ejecta; M1 simulations show systematically larger proton fractions, reaching maximum values larger than 0.4. r-process nucleosynthesis yields reflect the different ejecta compositions; they are in agreement and reproduce residual solar abundances only if M0 or M1 neutrino transport schemes are adopted. We compute kilonova light curves using spherically-symmetric radiation-hydrodynamics evolutions up to 15 d post-merger, finding that they are mostly sensitive to the ejecta mass and electron fraction; accounting for multiple ejecta components appears necessary for reliable light curve predictions. We conclude that advanced neutrino schemes and resolutions higher than current standards are essential for robust long-term evolutions and detailed astrophysical predictions.